Coping with centriole loss: pericentriolar material maintenance after centriole degeneration - Carla M. C. Abreu; Tiago J. Dantas (Communications Biology, 2021)
Shortly after the onset of ciliogenesis in Caenorhabditis elegans sensory neurons, the centrioles/basal bodies undergo degeneration. The fate of the pericentriolar material (PCM) that was associated with those centrioles has, however, remained unknown. Two recent studies by the Dammermann and the Feldman groups now show that not only does the PCM persist at the ciliary base, it also continues to assemble in the absence of canonical centrioles. Importantly, these neuronal centrosomes retain the ability to function as the cell’s main microtubule-organizing center and support ciliary function.